A stability-based model of a growing spine with adolescent idiopathic scoliosis: A combination of musculoskeletal and finite element approaches. (February 2019) - Kamal, Zeinab; Rouhi, Gholamreza; Arjmand, Navid; Adeeb, Samer
Highlights: Effects of stability-based muscle forces on scoliotic spine growth need to be known. Combined musculoskeletal and finite element models of growing trunks are developed. Results of the FE models agreed with the outcomes of in-vivo and in-vitro studies. Reaction moments in scoliotic spine amplified stresses on the posteroconcave side. Positive correleation between the spine height and Cobb angle growth-rates was seen. Abstract: Using a combined musculoskeletal and finite element (FE) approach, this study aimed to evaluate stability-based muscle forces in a spine with adolescent idiopathic scoliosis (AIS) as compared to a normal spine; and subsequently, determine the effects of stress distribution on the growth plates (GPs) of the growing spine. For this purpose a nonlinear 3D FE model of one normal and one scoliotic thoracolumbar spine, consisting of GPs attached to rigid L1 to L4 vertebrae, were developed using computed tomography images coupled with a growth modulation using the Stokes' model. Corresponding well with recent in-vivo and in-vitro studies, results of the models predicted intradiscal pressures at the L3-L4 and L4-L5 levels of 0.32 and 0.38 MPa in the normal spine and 0.30 and 0.36 MPa in the scoliotic spine, respectively; and hydrostatic and octahedral shear stresses on the apical GP of 0.11 and 0.06 MPa, respectively. The reaction moments in the scoliotic model resulted in higher compression on the posteroconcave side of the GPs, which led to deformity progression as predicted by the Hueter–Volkmann theory. Moreover, the augmented baseline growth in the Stokes' model magnified both the scoliotic spine height and Cobb angle growth rates. The presented stability-based approach can be used to predict the performance of rehabilitation strategies in the clinical management of AIS.